Tanzania HIV Investment Case (IC) 2.0: Using modeling to explore optimization under severe resource constraints - Stephen Resch; Lindsey Hiebert; Carl Schutte; Mohamed Turay; Leopold Zekeng; Sode Matiku; Iris Semini; John Stover; Steven Forsythe; Robert Hecht (Journal of Global Health Reports)
# Background